Histokomparatif Organ Integumen, Intestinum, Pohon Respirasi Pada Beberapa Jenis Teripang Dari Perairan Karimunjawa - Setia Nugroho, Gangsar Bayu; Hartati, Retno; Praseno, Koen (977-2407769)
Sea cucumbers, which have significant economic values, belong to the order of Aspidochirotida, with the two main family, i.e. Holothuriidae and Stichopodidae. Biological aspect of those species has not been exploited yet, therefore he aim of this research is to compare organ histology of the species of sea cucumbers H. atra, H. edulis, P. graeffei, S. chloronotus, and S. herrmanni. This research was held on August-December 2011 and histologically. The result of this research showed that integument of H. atra, H. edulis, P. graeffei, S. chloronotus, dan S. herrmanni consist of epidermis which composed by fibril cells and dermis layer which composed by connective tissue. Intestinum of Holothuriidae is different from Stichopodidae as follows : H. atra ±10 μm form a bugles with flat ends, S. chloronotus ±40 μm form a smooth bugles with pointed ends and closely, and S. herrmanni ±30 μm form a smooth bugles with pointed ends and distantly. The respiratory trees of Holothuriidae and Stichopodidae in general had similarity. Bases on these differences can be concluded that sea cucumbers cultivation techniques need adjustment habitat and consumption of different types of feed each sea cucumbers.